Prodrugs and drug delivery - Rautio, Jarkko (Henry Stewart Talks, 2013)
Prodrugs and drug delivery, Prodrug concept and designing prodrugs, Solving ADMET properties, Prevalence, recent approvals and best-sellers
Archived at 2022/07/31